SELF-CONCEPT ON TEENAGE STREET CHILDREN - Yudit Oktaria Kristiani Pardede (Jurnal Psikologi, 2007)
Street children phenomenon has grown old, but at this time into the world's attention, along with the increasing number of street children in many big cities in the world. This study aims to examine how the concept description Up the Streets Age Child and Adolescent why the concept of self can be created. The concept itself is a picture and descriptive evaluative individuals about themselves, or research on self-assessment, or how someone looked himself. According to Baldwin & Holmes (in Calhoun & Acocella 1995), the concept of self-forming factors is teenage parents, his contemporary, the community, and learning. The sample in this research is a street children who have dropped out of contact with their families, and participate fully in the streets, either social or economic. According to Patton (Poerwandari in 1998) a qualitative research could examine in depth the case of single (n = 1) is selected purposively. Based on the opinion, the research in this subject was one person. Techniques of data gathering is done by observation and interviews. According Poerwandari (1998), the interview is a discussion that focused on achieving a particular purpose. In this study, researcher uses non-participant observation method. According to Hadi (1986), observer does not perform consecutive observations at least in part the behavior of people - people who observed. From the results of the analysis of data, it is known that in general, the concept of self that the self is the subject of a negative self-concept. It can be seen from some of the subjects themselves who most look himself in the negative side. And it also can also be caused by several factors that shape self-concept to the negative direction, such as parents, friends of the, and the community.Key words: self-concept, street children